Pengaruh Pelatihan Kecerdasan Emosi terhadap Penurunan Agresivitas Anak di Sekolah - Herlina Sari; Irwan Nuryana Kurniawan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2004)
The purpose of this research is to examine empirically whether emotional intelligence training  was effective in reducing children aggression at school. This research used experimental method with  treatments by subject design, which involved 50 elementary school pupils in Yogyakarta as study participants. This research used children aggression scale to reveal the degree of children aggression at school. The result of this research suggests that emotional intelligence significantly was effective in reducing children aggression at school. Practical and research future implication are discussed.Key Words : Emotional Intelligence Training, Children Aggression at School